Antropologia da Saúde, Psiquiatria Transcultural e Etnopsiquiatria — Considerações Teóricas - Sousa, Teresa Rego de; Santinho, Maria Cristina (Trabalhos de Antropologia e Etnologia, 2020)
This article follows the theoretical analysis and the ethnographic work carried out in 2017 and 2018, condensed in the master's thesis in anthropology on mental health, transcultural psychiatry and asylum seekers/refugees. The analysis of the models of modern psychiatry and the importance of the role of anthropology (health) in the production of new theoretical formulations concerning "transculturality" in the clinic were sought here. It is important to emphasize that the interdisciplinarity of both areas is increasingly necessary, since the opposite has been revealed as leading to sterile transcultural practices that fragment the reality brought by immigrants, refugees and asylum seekers. It serves the present to emphasize the importance of this polymorphous discourse.